3D Chiral MetaCrystals. (1st December 2021) - Esposito, Marco; Manoccio, Mariachiara; Leo, Angelo; Cuscunà, Massimo; Sun, Yali; Ageev, Eduard; Zuev, Dmitry; Benedetti, Alessio; Tarantini, Iolena; Passaseo, Adriana; Tasco, Vittorianna
Abstract: Fine control of the chiral light–matter interaction at the nanoscale, by exploiting designed metamaterial architecture, represents a cutting‐edge craft in the field of biosensing, quantum, and classic nanophotonics. Recently, artificially engineered 3D nanohelices demonstrate programmable wide chiroptical properties by tuning materials and architecture, but fundamental diffractive aspects that are at the origin of chiral resonances still remain elusive. Here, a novel concept of a 3D chiral metacrystal, where the chiroptical properties are finely tuned by in‐plane and out‐of‐plane diffractive coupling, is proposed. Different chiral dipolar modes can be excited along the helix arms, generating far field optical resonances and radiation pattern with in‐plane side lobes, and suggesting that a combination of efficient dipole excitation and diffractive coupling matching controls the collective oscillations among the neighbor helices. The proposed concept of compact chiral metacrystal can be suitable for integration with quantum emitters and open perspectives in novel schemes of enantiomeric detection. Abstract : In 3D chiral metacrystals, the chiroptical properties can be finely tuned by in‐plane and out‐of‐plane diffractive coupling. The proposed concept could be suitable for integration with quantum emitters and open perspectives in novel schemes of enantiomeric detection.